DARA ANTA (SEBUAH TRAGEDI DARI LEGENDA MASYARAKAT KETUNGAU HILIR KABUPATEN SINTANG - Wanda, Apriyanti; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract?Dara Anta choreograph inspired by the legend of Ketungau Hilir?s people of Sintang District. Legend is a story that is considered true, the story is related to historical figures, it has been spiced with magic, wonders, and special features. The legend of Dara Anta is a tragedy that happened in the past, still a story until now among the peoples of Ketungau Hilir, when a woman named Dara Anta became a stone due to anger because of her husband?s betrayal. This phenomenom turns out to be the basic idea in creating